Determination of Nitrate Nitrogen and Nitrite Nitrogen in Brackish and Saline Waters by Flow Injection Analysis - Hongbin SUN; Huiyuan ZANG; Xin ZHANG; Yun ZHU; Lei WANG (Yankuang ceshi)
BACKGROUNDSaline water and brackish water resources are widely distributed, which are important alternative water resources in arid and semi-arid areas. They are also important sources of national strategic mineral resources such as lithium and potassium salts. Monitoring the key indicators such as nitrate and nitrite in saline water and brackish water is an important prerequisite for the comprehensive utilization of water resources. There are various methods for determining nitrates and nitrites, including spectrophotometry, fluorescence, chemiluminescence, electrochemistry, chromatography, and flow injection analysis. Among them, chromatography and electrochemistry require expensive and complex instruments or reagent; while spectrophotometry, although using simple equipment, has complex manual operation. Flow injection analysis is an analytical method that integrates sampling, enrichment, separation, and detection and can be used to achieve online detection and analysis. It has been widely used in freshwater and seawater analysis, but for saline water samples with higher salinity, the method has not been studied in depth.OBJECTIVESTo establish an analytical method for the determination of nitrate nitrogen and nitrite nitrogen in saline water and brackish water using a fully automatic flow injection analyzer to expand the scope of application of the instrument and achieve simultaneous determination of nitrate nitrogen and nitrite nitrogen in saline water, brackish water and freshwater.METHODAn analytical method suitable for the determination of nitrate nitrogen and nitrite nitrogen in saline and brackish water was established using a fully automatic flow injection analyzer after optimizing experimental conditions such as instrument working parameters, the affection of sulfonamide and N-(1-naphthyl) ethylenediamine concentration, the ammonium chloride concentration and pH value in buffer solution.RESULTSThe optimal instrumental operating conditions were selected through condition optimization experiments. The effects of chromogenic agent concentration and medium were investigated, as well as the buffer solution concentration and its pH value. Finally, sulfanilamide concentration was selected as 40g/L, hydrochloric acid-naphthyl ethylenediamine dihydrochloride concentration was selected as 1.0g/L as the optimal chromogenic concentration. Ammonium chloride concentration was selected as 60g/L, and the pH value was set to 8.5 to configure buffer solution. Under this condition, cadmium column had a reduction rate of more than 95% for nitrate nitrogen. Using pure water as carrier flow, this method can be used to accurately determine the content of nitrate nitrogen and nitrite nitrogen in water samples with salinity ranging from 0 to 5%. When the carrier flow was configured to have the same salinity as the sample to be tested, it effectively improved the recovery efficiency of high-salinity samples and extended the tolerance range of this method to about 24% salinity. The detection limits of nitrate nitrogen and nitrite nitrogen were 0.002mg/L and 0.001mg/L, respectively, with measurement ranges of 0-2.00mg/L and 0-1.00mg/L. The analysis results of national standard substances and actual samples show that this method has good precision and accuracy, as well as a high degree of automation and short analysis cycle, which are suitable for the analysis of large quantities of samples.CONCLUSIONA method for the determination of nitrate nitrogen and nitrite nitrogen in saline water and brackish water samples was established. This method can be used to accurately determine the content of nitrate nitrogen and nitrite nitrogen in brackish water and saline water to achieve efficient online automation analysis.